Moneyers of the late Anglo-Saxon coinage, 1016-1042 - Smart, Veronica (1981)
A previous study of the moneyers' names on the late Anglo- Saxon coinage by the same writer concluded with the death of Ethelred Il. This study continues the survey to the accession of Edward the Confessor. The introduction summarises the sources for the coins of this period, current research on their dating and die-cutting, and the function of double names which appear on the coins.